Drug treatment for chronic hepatitis C infection and cancer risk: the effect of direct antivirals on the incidence and recurrence of hepatocellular carcinoma - Wörns, Marcus-Alexander; Schirmacher, Peter (Deutsches Ärzteblatt, 2017)
Background In patients with chronic hepatitis C infection, a sustained virologic response (SVR) to interferon-based therapy markedly decreases the incidence of hepatocellular carcinoma (HCC) over the long term. This is also true for patients who have hepatic cirrhosis, as well as for those with HCC—with or without cirrhosis—who have undergone resection or ablation with curative intent. Recent publications, however, have reported a higher incidence of HCC among patients in both of these subgroups who were treated with direct antiviral agents (DAA) rather than interferon-based therapy. Methods A selective search for pertinent literature was carried out in the PubMed database with the search terms “direct-acting antiviral therapy” and “hepatocellular carcinoma.” Results In comparison to historical patient cohorts that received interferon-based therapy, patients with hepatic cirrhosis after SVR brought about by DAA have a higher incidence of de novo HCC in 12 months (5.2-7.4%). The recurrence rate after treatment for HCC with curative intent was also higher, with marked fluctuations. Patients treated with DAA were often older and in a more advanced stage of cirrhosis than those who had received interferon-based therapy; these factors may have contributed to the observed higher incidence of HCC. On the other hand, the reduction of inflammation-triggered immune surveillance after very rapid elimination of the hepatitis C virus may have favored tumor progression. Conclusion Before DAA therapy is initiated in a patient who has cirrhosis or has undergone treatment for HCC with curative intent, a de novo or recurrent HCC should be meticulously excluded. Even after SVR, these patients still need intensive follow-up and surveillance.